EFFECT OF WELDED STRUCTURE ON THE STRENGTH OF THE AIRHSIP MEMBRANE - CHEN Zheng; ZHAO HaiTao; HUANG JiPing; CHEN JiAn (Jixie qiangdu)
In order to investigate the material properties of the welded structure in the airship and the effect of the welded structure on the membrane strength,the test specimens and schemes were designed for uniaxial tensile test,uniaxial cyclic test,and biaxial tensile test according to the airship engineering experience and structural stress distribution. The method of digital image correlation was adopted in the experiment. The test results show that the strength of welded structure is more than membrane and the fracture location is the membrane where the two materials meet. The strength of membrane with welded structure is smaller than the membrane itself,which is reduced by about 12% under uniaxial tensile condition and reduced by about 36% under biaxial tensile condition with ratio 2 ∶1. This paper can provide experimental support for the strength prediction of the airship structure.